Processo de trabalho da equipe de saúde da família na atenção às urgências e emergências: limites e possibilidades - Levi, Tacila Machado (2018)
The development of the Family Health Team Work Process in the attention to Emergencies has the user at the center of attention and establishes the dynamic relationship between nurses, doctors, nursing technicians and community health agents (agents), who interact with the user and their acute or chronic acute needs (object), health care consumer (product), at the exact moment of its production. It uses instruments, lightweight, hard and hard technologies, such as bonding, qualified listening, reception, knowledge, equipment and materials, with the purpose of solving the urgency and emergency needs brought by these users.This study aims to analyze the development of the work process of the Family Health Team in the attention to emergencies and emergencies; and describe the limits and possibilities for the development of the work process of the Family Health Team in the attention to Emergencies and Emergencies. This is a case study, qualitative and exploratory, which had as a research field a Family Health Unit of the Liberdade Sanitary District in the city of Salvador-Ba.The techniques of data collection were systematic observation and semi-structured interview. There were 24 participants in the research. After a careful reading of the data, the following categories were found: Family Health Team work process in dealing with emergencies and emergencies; Limits and possibilities for the development of the work process of the Family Health Team in the attention to emergencies and emergencies.The data were presented, analyzed and discussed using the Bardin Content Analysis technique. The Family Health Team's work process in dealing with emergencies and emergencies is developed in a fragile and fragmented way. The barriers to access, coupled with the lack of access to the instruments of the work process and the staff's understanding of emergencies and emergencies, the absence of the Reception with Risk Classification in the service, Permanent Education in Incipient Health, led to the practice of referral of the demands of urgency and emergency to other levels of attention, characterizing the Basic Attention as preferential door of access to the Network of Attention to Health.We conclude that the structural limits of equipment, materials, lack of internal flow, disarticulation with the Network, low coverage of the municipality by the Family Health Strategy, incompleteness of the teams and the Management's own view in the Family Health Strategy make it difficult to urgencies and emergencies by the Family Health Team. The well-being in teamwork and the dynamic practice of the Unit Manager were signaled as a favorable contribution to the development of the work process. The visibility of limits constitutes a power for advancement, contributing to the construction of a Family Health Strategy, which allows better accessibility and solvency of spontaneous and programmed demands, with optimization of resources of medium and high complexity, being more equitable, integral and universal